Development of a Laboratory Model Retaining Wall Test Facility. - Chow , Shiao Huey; Chow , Shiao Teng; Abdul Ghani, Abdul Naser; Ibrahim, Anas (2008)
In an attempt to investigate the effectiveness of cement bound waste material geocomposite stabilised retaining wall, a laboratory model wall test facility has been developed.